Is There a Decrease in the Amount of Vocabulary of Freshmen in Higher Education? Longitudinal Analysis - Zapico, Martín Gonzalo (2019)
In the Argentine education system today, we live a crisis situation, which becomes evident when high school graduates must face a college degree: they do not have the basic skills of reading and writing, which results in a high dropout rate in their freshman year. In turn, there are ideas that affirm a decrease in these competences throughout the years and the new cohorts. In this article, we will test this hypothesis. Hence, the scores obtained in a vocabulary test will be compared to four cohorts of new students, and the changes in the scores will be observed. The results suggest a slow but constant decrease in the means of the results, although there is no statistically significant difference between the cohorts and the scores.